A high barrier type easy linear tearing polyethylene film and its preparation process

Through the five-layer coextruded film blow molding process, a high-barrier type, linear tear-tearing polyethylene film is prepared by combining cyclic olefin copolymers with light-blocking functional groups with polyethylene resin, which solves the problems of poor barrier properties and difficulty in tearing in the existing films, and achieves excellent barrier and tear properties.

CN119058202BActive Publication Date: 2025-03-11SUZHOU ZIJIN PLASTIC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411546659.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-11
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing polyethylene film has poor barrier properties, which shortens the shelf life of medicines or foods, and the packaging bags are not easy to tear, resulting in inconvenience in use.

Method used

The five-layer coextruded film blow molding process is used to combine the cyclic olefin copolymer COC resin and the sheet-layer spacing stable montmorillonite with the light-blocking functional group with polyethylene resin to prepare a high-barrier, linear tear polyethylene film.

Benefits of technology

The barrier properties and linear tear properties of the film are improved, the oxygen permeability and water vapor permeability are reduced, and the light transmittance and longitudinal tear deviation are also improved, meeting the dual requirements of high barriers and easy tear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119058202B_ABST
    Figure CN119058202B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional polyethylene films, and discloses a high-barrier polyethylene film that is easy to tear in a straight line and a preparation process thereof, comprising: designing a film structure of the high-barrier polyethylene film that is easy to tear in a straight line; performing intercalation modification treatment on sodium-based montmorillonite using a quaternary ammonium salt reagent carrying a light-blocking functional group, loading the light-blocking functional group on the surface of a montmorillonite nanosheet, and preparing a montmorillonite with a stable interlayer spacing carrying the light-blocking functional group; using a cyclic olefin copolymer COC resin and a montmorillonite with a stable interlayer spacing as raw materials for easy-tear barrier function modification, compounding them with a polyethylene resin under the action of liquid paraffin, and preparing an organic-inorganic composite easy-tear barrier composition; performing functional modification treatment on a polyethylene resin using the organic-inorganic composite easy-tear barrier composition, and adopting a co-extrusion blow molding method to prepare a high-barrier polyethylene film product that is easy to tear in a straight line, and the film product has excellent barrier performance and linear tearing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional polyethylene films, in particular to a high-barrier polyethylene film that is easy to tear linearly and a preparation process thereof. Background Art

[0002] Polyethylene film is a film made of polyethylene resin as the main raw material by cast film or blow molding. It is heat-sealed and cut into polyethylene bags for packaging of solid raw materials, food additives, etc. However, its main disadvantage is its poor barrier properties, which shortens the shelf life of drugs or foods.

[0003] With the continuous improvement of packaging technology, consumers are no longer satisfied with the simple necessary functions of food packaging such as protecting food and extending the shelf life of food, but have put forward higher and higher requirements for the ease of use of food packaging in actual use. Among them, the tearability of packaging is one of the practical functions that consumers pay more attention to. Easy-tear packaging bags are generally made of easy-tear and easy-opening films, and are equipped with easy-tear openings. The easy-tear of easy-tear packaging bags means that they can be torn from the easy-tear opening, and the tear is straight.

[0004] Currently, one way to obtain linear tear properties is by blending a polymer with a tear modifier, that is, another way is to prepare it by multi-layer co-extrusion combined with a biaxial stretching process.

[0005] Although easy-tear films have been widely used in packaging, in real life there are still cases where packaging bags are difficult to tear. For example, the sauce packets included in convenience foods are often difficult to tear or the contents splash during the tearing process. Summary of the invention

[0006] The present invention provides a process for preparing a high-barrier polyethylene film that is easy to tear linearly. The film product prepared thereby has excellent barrier properties on the one hand, and its linear tearing property meets the technical requirements of very good linear tearing property specified in industry standards on the other hand.

[0007] A high barrier type polyethylene film that is easy to tear in a straight line, the film structure of the high barrier type polyethylene film that is easy to tear in a straight line is:

[0008] The formula of the first layer is 100wt% low-density polyethylene resin LDPE, and the dosage of this layer is 20-40 parts by weight;

[0009] The formula of the second layer is 100wt% maleic anhydride grafted low-density polyethylene resin PE-g-MAH, and the amount of this layer is 5-15 parts by weight;

[0010] The formula of the third layer is 40-60wt% low-density polyethylene resin LDPE + 40-60wt% organic-inorganic composite easy-tear barrier composition, and the amount of this layer is 10-30 parts by weight;

[0011] The formula of the organic-inorganic composite tearable barrier composition is: 25-35wt% low-density polyethylene resin LDPE, 15-25wt% linear low-density polyethylene resin LLDPE, 35-45wt% cyclic olefin copolymer COC resin, 5-10wt% interlamellar spacing stabilized montmorillonite carrying light-blocking functional groups, and 1-3wt% liquid paraffin;

[0012] The preparation method of the interlayer spacing-stabilized montmorillonite carrying light-blocking functional groups is as follows: a quaternary ammonium salt reagent carrying light-blocking functional groups is used to perform intercalation modification on sodium-based montmorillonite, wherein the ammonium cations of the quaternary ammonium salt reagent and the interlayer sodium cations of the sodium-based montmorillonite first undergo ion exchange, and then the light-blocking functional groups are loaded on the surface of the montmorillonite nanosheets through electrostatic action;

[0013] The quaternary ammonium salt reagent is a quaternary ammonium salt monomer Ma or a compound quaternary ammonium salt;

[0014] The compound quaternary ammonium salt is composed of equal parts by weight of a quaternary ammonium salt monomer Ma and a quaternary ammonium salt monomer Mb;

[0015] The fourth layer is formulated with 100 wt% maleic anhydride grafted low-density polyethylene resin PE-g-MAH, and the amount of this layer is 5-15 parts by weight;

[0016] The formula of the fifth layer is 40-60wt% low-density polyethylene resin LDPE+40-60wt% linear low-density polyethylene resin LLDPE, and the usage of this layer is 20-40 parts by weight.

[0017] Preferably, the preparation method of the quaternary ammonium salt monomer Ma is: an amine-ene addition reaction is carried out between the -NH2 functional group of 2,2,6,6-tetramethylpiperidinamine and the alkenyl functional group of acryloyloxyethyltrimethylammonium chloride, and the molar ratio of 2,2,6,6-tetramethylpiperidinamine and acryloyloxyethyltrimethylammonium chloride is controlled to be (1.01-1.05):1, thereby preparing the quaternary ammonium salt monomer Ma.

[0018] Preferably, the preparation method of the quaternary ammonium salt monomer Mb is: an amine-ene addition reaction is carried out between the -NH2 functional group of 2,2,6,6-tetramethylpiperidinamine and the alkenyl functional group of acryloyloxyethyltrimethylammonium chloride, and the molar ratio of 2,2,6,6-tetramethylpiperidinamine and acryloyloxyethyltrimethylammonium chloride is controlled to be 1:(2.01-2.05), thereby preparing the quaternary ammonium salt monomer Mb.

[0019] Preferably, the mass ratio of the quaternary ammonium salt reagent carrying light-blocking functional groups to the sodium-based montmorillonite in the interlamellar spacing-stabilized montmorillonite carrying light-blocking functional groups is 1:(1-5).

[0020] Preferably, the flake diameter of the sodium-montmorillonite is 2-5 μm and the thickness is 3-8 nm.

[0021] Preferably, the oxygen permeability of the high barrier type easy linear tearing polyethylene film is (0.5-1.0) cm 3 / (m 2 •24h•0.1MPa), water vapor permeability is (1.0-1.5)g / (m 2 •24h), light transmittance is 30~40%, and longitudinal tear deviation is 7.0-9.0%.

[0022] A preparation process of a high-barrier linearly tearable polyethylene film comprises the following steps:

[0023] Step 1, preparing an organic-inorganic composite easy-tear barrier composition: preparing ingredients according to the formula of the organic-inorganic composite easy-tear barrier composition, adding the formula raw materials into a high-speed mixer and mixing them evenly, and extruding and granulating them through a twin-screw extruder to prepare an organic-inorganic composite easy-tear barrier composition;

[0024] Step 2, prepare a high-barrier polyethylene film that is easy to tear in a straight line: prepare the ingredients according to the formula of the high-barrier polyethylene film that is easy to tear in a straight line, and put the raw materials of each layer into the hoppers of the five screw extruders of the five-layer co-extrusion film blow molding unit respectively. After stirring and mixing, the molten resin is converged at the head of the machine through a diverter, and is extruded and blow-molded through a die head. The blow ratio is controlled at 2.5-2.9, and the film is cooled and rolled to prepare a high-barrier polyethylene film that is easy to tear in a straight line with a thickness of 50-150μm.

[0025] Preferably, the process parameters of the twin-screw extruder in step 1 are set as follows: the temperatures of zones 1-6 are 160-170°C, 165-175°C, 170-180°C, 175-185°C, 175-185°C, 180-190°C, respectively, and the rotation speed is 200-400r / min;

[0026] Preferably, the process parameters of the screw extruder corresponding to the first and fifth layers in the step 2 are set as follows: the temperatures in zones 1-3 are 100-120°C, 140-150°C, and 150-170°C, respectively, the flow channel temperature is 145-155°C, and the speed is 30-40r / min; the process parameters of the screw extruder corresponding to the second and fourth layers are set as follows: the temperatures in zones 1-3 are 110-120°C, 140-150°C, and 150-170°C, respectively, the flow channel temperature is 145-155°C, and the speed is 10-20r / min; the process parameters of the screw extruder corresponding to the third layer are set as follows: the temperatures in zones 1-3 are 170-190°C, 200-220°C, and 220-240°C, respectively, the flow channel temperature is 215-225°C, and the speed is 40-60r / min.

[0027] The present invention uses cyclic olefin copolymer COC resin and interlamellar spacing-stabilized montmorillonite carrying light-blocking functional groups as raw materials for easy-tear barrier function modification, and compounds them with polyethylene resin under the action of liquid paraffin to prepare an organic-inorganic composite easy-tear barrier composition;

[0028] The organic-inorganic composite easy-tear barrier composition was used to perform functional modification on polyethylene resin, and a high-barrier, easy-to-tear polyethylene film product was prepared by co-extrusion blow molding. The oxygen permeability of the film product was reduced to 1.0 cm 3 / (m 2 •24h•0.1MPa), water vapor permeability decreased to 1.5g / (m 2 •24h), the transmittance decreased to 40% and the longitudinal tear deviation decreased to 9.0%. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 These are the performance test results of high barrier and easy linear tearing polyethylene film. DETAILED DESCRIPTION

[0030] The main raw materials used in the present invention are as follows:

[0031] Low-density polyethylene resin LDPE was purchased from Jiangsu Rantai Plastics Co., Ltd., and its brand is LD 150DW;

[0032] Maleic anhydride grafted polyethylene resin PE-g-MAH was purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd., with the brand number 4288;

[0033] Linear low-density polyethylene resin LLDPE was purchased from Yuyao Hongyang Plastic Chemical Co., Ltd., with the brand number 2045G;

[0034] Cyclic olefin copolymer COC resin was purchased from Dongguan Tianzhihong Plastic Chemical Co., Ltd., and its model is TOPAS6013M-07;

[0035] Sodium montmorillonite was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with the following specifications: flake diameter 2-5 μm, thickness 3-8 nm. Embodiment 1:

[0036] A high barrier type linearly tearable polyethylene film, the film structure of which is:

[0037] The formula of the first layer is 100wt% low-density polyethylene resin LDPE, and the amount of this layer is 30 parts by weight;

[0038] The formula of the second layer is 100wt% maleic anhydride grafted low-density polyethylene resin PE-g-MAH, and the amount of this layer is 10 parts by weight;

[0039] The formula of the third layer is 50wt% low-density polyethylene resin LDPE + 50wt% organic-inorganic composite easy-tear barrier composition, and the amount of this layer is 20 parts by weight; wherein the formula of the organic-inorganic composite easy-tear barrier composition is: 30wt% low-density polyethylene resin LDPE, 20wt% linear low-density polyethylene resin LLDPE, 40wt% cyclic olefin copolymer COC resin, 8wt% interlamellar spacing stabilized montmorillonite carrying light-blocking functional groups, and 2wt% liquid paraffin;

[0040] The interlamellar spacing-stabilized montmorillonite carrying light-blocking functional groups is interlamellar spacing-stabilized montmorillonite I or interlamellar spacing-stabilized montmorillonite II. The preparation method of interlamellar spacing-stabilized montmorillonite I is recorded in Experimental Example I, and the preparation method of interlamellar spacing-stabilized montmorillonite II is recorded in Experimental Example II.

[0041] The fourth layer has a formula of 100 wt% maleic anhydride grafted low-density polyethylene resin PE-g-MAH, and an amount of 10 parts by weight;

[0042] The formula of the fifth layer is 50wt% low-density polyethylene resin LDPE+50wt% linear low-density polyethylene resin LLDPE, and the amount of this layer is 30 parts by weight. Embodiment 2:

[0043] The preparation process of a high barrier type linearly tearable polyethylene film in Example 1 includes the following specific steps:

[0044] Step 1: preparing an organic-inorganic composite tearable barrier composition, the specific process is as follows:

[0045] The ingredients are prepared according to the formula of the organic-inorganic composite easy-tear barrier composition, the formula raw materials are added into a high-speed mixer and mixed evenly, and the mixture is extruded and granulated by a twin-screw extruder to prepare the organic-inorganic composite easy-tear barrier composition;

[0046] Among them, the process parameters of the twin-screw extruder were set as follows: the temperatures of zones 1-6 were 165°C, 170°C, 175°C, 180°C, 180°C, and 185°C, respectively, and the rotation speed was 300r / min;

[0047] Step 2: prepare a high barrier polyethylene film that is easy to tear linearly, and the specific process is as follows:

[0048] The ingredients were prepared according to the formula of the high-barrier and easy-to-tear polyethylene film, and the raw materials of each layer were respectively put into the hoppers of the five screw extruders of the five-layer co-extrusion film blow molding unit. After stirring and mixing, the molten resin was merged at the head of the die through a splitter, and was extruded and blown through a die head. The blow-up ratio was controlled at 2.7, and the film was cooled and rolled to prepare a high-barrier and easy-to-tear polyethylene film with a thickness of 80 μm.

[0049] Among them, the process parameters of the screw extruder corresponding to the first and fifth layers are set as follows: the temperatures of zones 1-3 are 110°C, 145°C, and 160°C, respectively, the flow channel temperature is 150°C, and the speed is 35r / min;

[0050] The process parameters of the screw extruders corresponding to the second and fourth layers were set as follows: the temperatures of zones 1-3 were 115°C, 145°C, and 160°C, respectively, the flow channel temperature was 150°C, and the rotation speed was 15 r / min;

[0051] The process parameters of the screw extruder corresponding to the third layer are set as follows: the temperatures of zones 1-3 are 180°C, 210°C, and 230°C, respectively, the flow channel temperature is 220°C, and the speed is 50r / min;

[0052] When the interlamellar spacing-stabilized montmorillonite carrying light-blocking functional groups is interlamellar spacing-stabilized montmorillonite I, the prepared film product is recorded as high-barrier easy-to-tear linear polyethylene film I;

[0053] When the interlamellar spacing-stabilized montmorillonite carrying light-blocking functional groups is interlamellar spacing-stabilized montmorillonite II, the prepared film product is recorded as high-barrier and easily linearly tearable polyethylene film II.

[0054] Comparative Example:

[0055] Preparation of pure polyethylene film: The difference between its preparation process and the preparation process of high-barrier easy-to-tear linear polyethylene film is that no organic-inorganic composite easy-to-tear barrier composition is used.

[0056] Performance Test:

[0057] The performance of high barrier and easy linear tearing polyethylene film samples was tested, and the experimental results are shown in Table 1 and Figure 1 shown.

[0058] Table 1 Performance test results of high barrier and easy linear tearing polyethylene film

[0059] Sample Type Performance Specifications High barrier type easy to tear linear polyethylene film Ⅰ High barrier type easy to tear linear polyethylene film Ⅱ Comparative Example Testing standards <![CDATA[Oxygen permeability [cm 3 / (m 2 •24h•0.1MPa)]]]> 0.9 0.8 5.4 GB / T 1038-2000 <![CDATA[Water vapor transmission rate [g / (m 2 •24 h)]]]> 1.4 1.2 5.6 GB / T 1037-2021 Light transmittance(%) 38.2 35.7 75.8 GB / T 2410-2008 Longitudinal tensile strength (MPa) 32.3 36.5 28.3 GB / T 13022-1991 Longitudinal tear deviation (%) 7.4 8.6 63.4 /

[0060] Note: The test method for linear tearing performance is: cut a crack in the middle of the sample with a length of L and a width of W in the width direction, tear the film uniformly along the crack direction, measure the width W' at the other end of the film, and calculate the tearing deviation of the sample. The specific calculation method is as follows:

[0061] Tearing deviation (%) = (W / 2-W') / (W / 2) × 100%;

[0062] The current industry standard for linear tear performance is: when the tear deviation is <10%, the linear tear performance is considered very good; when 10%≤tear deviation≤30%, the linear tear performance is considered good; when the tear deviation is >30%, the linear tear performance is considered poor;

[0063] The following conclusions can be drawn from the experimental results:

[0064] First, the high barrier and easy linear tear polyethylene film products prepared by the present invention meet the technical requirements of excellent linear tearing properties stipulated in the industry standards;

[0065] Second: The high-barrier and easy-to-tear linear polyethylene film product prepared by the present invention not only has very excellent barrier properties, but also has better light-blocking ability, and the mechanical properties are also significantly improved.

[0066] Experimental Example I:

[0067] Preparation of interlamellar spacing-stable montmorillonite I: sodium-based montmorillonite is intercalated and modified by using a quaternary ammonium salt monomer Ma carrying a light-blocking functional group (hindered amine group). The ammonium cation of the quaternary ammonium salt monomer Ma and the interlayer sodium cation of the sodium-based montmorillonite first undergo ion exchange, and then the light-blocking functional group is loaded on the surface of the montmorillonite nanosheet through electrostatic action to prepare interlamellar spacing-stable montmorillonite I. The specific preparation steps are as follows: 5g of sodium-based montmorillonite and 100mL of anhydrous ethanol are added to a three-necked flask, ultrasonicated for 30min, heated to 70°C and stirred for 2h, then 20mL of anhydrous ethanol solution containing 2g of quaternary ammonium salt monomer Ma is added to the three-necked flask, stirred and reacted at 70°C for 4h, filtered, washed with anhydrous ethanol until no precipitation is detected by silver nitrate solution, and vacuum dried at 60°C for 12h to obtain interlamellar spacing-stable montmorillonite I;

[0068] The preparation method of the quaternary ammonium salt monomer Ma is as follows: an amine-ene addition reaction is carried out between the -NH2 functional group of 2,2,6,6-tetramethylpiperidinamine and the olefinic functional group of acryloyloxyethyltrimethylammonium chloride, and the molar ratio of 2,2,6,6-tetramethylpiperidinamine to acryloyloxyethyltrimethylammonium chloride is controlled to be 1.04:1, thereby generating the quaternary ammonium salt monomer Ma, whose chemical structure is as follows:

[0069] ;

[0070] The synthetic experimental steps of the quaternary ammonium salt monomer Ma are as follows: 1.6 g (2,2,6,6-tetramethyl-piperidin-4-yl)-methylamine and 30 mL N,N-dimethylformamide are added to a three-necked flask, stirred at room temperature until completely dissolved, then 10 mL of acryloyloxyethyl trimethyl ammonium chloride solution (prepared from 1.9 g acryloyloxyethyl trimethyl ammonium chloride and 10 mL N,N-dimethylformamide) is added dropwise to the three-necked flask, stirred and mixed at room temperature for 30 minutes, heated to 40° C. and stirred for reaction for 5 hours, the solvent is removed by rotary evaporation, washed with N,N-dimethylformamide and deionized water in turn, and vacuum dried to obtain the quaternary ammonium salt monomer Ma;

[0071] The nuclear magnetic resonance hydrogen spectrum of the quaternary ammonium salt monomer Ma is characterized as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 1.20 (s, 6H), 1.25 (s, 6H), 1.56-1.65 (m, 4H), 1.96 (s, 1H), 2.49-2.53 (t, 2H), 3.05-3.16(m, 4H), 3.44(s, 9H), 3.65-3.68(t, 2H), 4.34-4.38(t, 2H).

[0072] Experimental Example II:

[0073] Preparation of interlayer spacing-stable montmorillonite II: using quaternary ammonium salt monomers Ma and Mb carrying light-blocking functional groups (hindered amine groups) to perform intercalation modification on sodium-based montmorillonite, the ammonium cations of the quaternary ammonium salt monomers Ma and Mb first undergo ion exchange with the interlayer sodium cations of the sodium-based montmorillonite, and then the light-blocking functional groups are loaded on the surface of the montmorillonite nanosheets through electrostatic action, so as to prepare interlayer spacing-stable montmorillonite II. The specific preparation method thereof refers to the preparation method of interlayer spacing-stable montmorillonite I, and the difference is only that: 2g of the quaternary ammonium salt monomer Ma is replaced by 1g of the quaternary ammonium salt monomer Ma and 1g of the quaternary ammonium salt monomer Mb;

[0074] The preparation method of the quaternary ammonium salt monomer Mb is as follows: an amine-ene addition reaction is carried out between the -NH2 functional group of 2,2,6,6-tetramethylpiperidinamine and the olefinic functional group of acryloyloxyethyltrimethylammonium chloride, and the molar ratio of 2,2,6,6-tetramethylpiperidinamine to acryloyloxyethyltrimethylammonium chloride is controlled to be 1:2.02, thereby generating the quaternary ammonium salt monomer Mb, whose chemical structure is as follows:

[0075] ;

[0076] The synthesis experiment of the quaternary ammonium salt monomer Mb refers to the synthesis experiment of the quaternary ammonium salt monomer Ma, and the difference is only that 1.9 g of acryloyloxyethyl trimethyl ammonium chloride is replaced by 4.0 g of acryloyloxyethyl trimethyl ammonium chloride;

[0077] The nuclear magnetic resonance hydrogen spectrum of the quaternary ammonium salt monomer Mb is characterized as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 1.18 (s, 6H), 1.26 (s, 6H), 1.76-1.77 (d, 4H), 1.98 (s, 1H), 2.51-2.55 (t, 4H), 2.74 -2.79 (m, 1H), 3.03-3.06 (t, 4H), 3.43 (s, 18H), 3.65-3.69 (t, 4H), 4.33-4.36 (t, 4H).

Claims

1. A high barrier type easy linear tearing polyethylene film, characterized in that: The film structure of the high barrier type easy linear tearing polyethylene film is: The formula of the first layer is 100wt% low-density polyethylene resin LDPE, and the dosage of this layer is 20-40 parts by weight; The formula of the second layer is 100wt% maleic anhydride grafted low-density polyethylene resin PE-g-MAH, and the amount of this layer is 5-15 parts by weight; The formula of the third layer is 40-60wt% low-density polyethylene resin LDPE + 40-60wt% organic-inorganic composite easy-tear barrier composition, and the amount of this layer is 10-30 parts by weight; The formula of the organic-inorganic composite tearable barrier composition is: 25-35wt% low-density polyethylene resin LDPE, 15-25wt% linear low-density polyethylene resin LLDPE, 35-45wt% cyclic olefin copolymer COC resin, 5-10wt% interlamellar spacing stabilized montmorillonite carrying hindered amine groups, and 1-3wt% liquid paraffin; The preparation method of the interlayer-spacing-stabilized montmorillonite carrying hindered amine groups is as follows: a quaternary ammonium salt reagent carrying hindered amine groups is used to perform intercalation modification on sodium-based montmorillonite, wherein the ammonium cations of the quaternary ammonium salt reagent and the interlayer sodium cations of the sodium-based montmorillonite first undergo ion exchange, and then the hindered amine groups are loaded on the surface of the montmorillonite nanosheets through electrostatic action; The quaternary ammonium salt reagent is a composite quaternary ammonium salt; The compound quaternary ammonium salt is composed of equal parts by weight of a quaternary ammonium salt monomer Ma and a quaternary ammonium salt monomer Mb; The fourth layer is formulated with 100 wt% maleic anhydride grafted low-density polyethylene resin PE-g-MAH, and the amount of this layer is 5-15 parts by weight; The formula of the fifth layer is 40-60wt% low-density polyethylene resin LDPE + 40-60wt% linear low-density polyethylene resin LLDPE, and the amount of this layer is 20-40 parts by weight; The chemical structural formula of the quaternary ammonium salt monomer Ma is: ; The chemical structural formula of the quaternary ammonium salt monomer Mb is: 。 2. A high barrier type linearly tearable polyethylene film according to claim 1, characterized in that: The preparation method of the quaternary ammonium salt monomer Ma is as follows: an amine-ene addition reaction is carried out between the -NH2 functional group of 2,2,6,6-tetramethylpiperidinamine and the alkenyl functional group of acryloyloxyethyltrimethylammonium chloride, and the molar ratio of 2,2,6,6-tetramethylpiperidinamine to acryloyloxyethyltrimethylammonium chloride is controlled to be (1.01-1.05):1, thereby preparing the quaternary ammonium salt monomer Ma.

3. The high barrier type easy linear tearing polyethylene film according to claim 1, characterized in that: The preparation method of the quaternary ammonium salt monomer Mb is as follows: an amine-ene addition reaction is carried out between the -NH2 functional group of 2,2,6,6-tetramethylpiperidinamine and the olefinic functional group of acryloyloxyethyltrimethylammonium chloride, and the molar ratio of 2,2,6,6-tetramethylpiperidinamine to acryloyloxyethyltrimethylammonium chloride is controlled to be 1:(2.01-2.05), so as to prepare the quaternary ammonium salt monomer Mb.

4. The high barrier type easy linear tearing polyethylene film according to claim 1, characterized in that: The mass ratio of the quaternary ammonium salt reagent carrying hindered amine groups to the sodium-based montmorillonite in the interlamellar spacing-stabilized montmorillonite carrying hindered amine groups is 1:(1-5).

5. The high barrier type linearly tearable polyethylene film according to claim 4, characterized in that: The sodium montmorillonite has a sheet diameter of 2-5 μm and a thickness of 3-8 nm.

6. The high barrier type easy linear tearing polyethylene film according to claim 1, characterized in that: The oxygen permeability of the high barrier type easy linear tearing polyethylene film is (0.5-1.0) cm 3 / (m 2 •24h•0.1MPa), water vapor permeability is (1.0-1.5)g / (m 2 •24h), light transmittance is 30~40%, and longitudinal tear deviation is 7.0-9.0%.

7. A process for preparing a high barrier type easy linear tearing polyethylene film according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, preparing an organic-inorganic composite easy-tear barrier composition: preparing ingredients according to the formula of the organic-inorganic composite easy-tear barrier composition, adding the formula raw materials into a high-speed mixer and mixing them evenly, and extruding and granulating them through a twin-screw extruder to prepare an organic-inorganic composite easy-tear barrier composition; Step 2, prepare a high-barrier polyethylene film that is easy to tear in a straight line: prepare the ingredients according to the formula of the high-barrier polyethylene film that is easy to tear in a straight line, and put the raw materials of each layer into the hoppers of the five screw extruders of the five-layer co-extrusion film blow molding unit respectively. After stirring and mixing, the molten resin is converged at the head of the machine through a diverter, and is extruded and blow-molded through a die head. The blow ratio is controlled at 2.5-2.9, and the film is cooled and rolled to prepare a high-barrier polyethylene film that is easy to tear in a straight line with a thickness of 50-150μm.

8. The process for preparing a high barrier type linearly tearable polyethylene film according to claim 7, characterized in that: The process parameters of the twin-screw extruder in step 1 are set as follows: the temperatures of zones 1-6 are 160-170° C., 165-175° C., 170-180° C., 175-185° C., 175-185° C., 180-190° C., respectively, and the rotation speed is 200-400 r / min; The process parameters of the screw extruders corresponding to the first and fifth layers in the step 2 are set as follows: the temperatures in zones 1-3 are 100-120°C, 140-150°C, and 150-170°C, respectively, the flow channel temperature is 145-155°C, and the rotation speed is 30-40r / min; the process parameters of the screw extruders corresponding to the second and fourth layers are set as follows: the temperatures in zones 1-3 are 110-120°C, 140-150°C, and 150-170°C, respectively, the flow channel temperature is 145-155°C, and the rotation speed is 10-20r / min; the process parameters of the screw extruder corresponding to the third layer are set as follows: the temperatures in zones 1-3 are 170-190°C, 200-220°C, and 220-240°C, respectively, the flow channel temperature is 215-225°C, and the rotation speed is 40-60r / min.

Citation Information

Patent Citations

  • High-barrier PE film with antibacterial function and preparation method thereof

    CN115257107A

  • Linear easy-to-tear steaming-resistant polyolefin film as well as preparation method and application of linear easy-to-tear steaming-resistant polyolefin film

    CN116353172A

  • Packaging material and double-body packaging bag

    CN118307868A